ANALISIS PROSES TOLAQ DALAM ISLAM - Siregar, Dame (FITRAH:Jurnal Kajian Ilmu-ilmu Keislaman, 2014)
Abstract: The cause of the permissibility of divorce from a husband is disharmony in the household, moral and moral crisis, adultery, marriage without love, protracted strife, pain parmanen, imprisonment of 5 years and over, are not able to do a conjugal relationship, barren wife, is not capable of implement the law of Allah Almighty, the wife of the ungodly. Tolaq khula cause other anatar bolehnya husband gets imprisonment for 5 years and over, and the wife can not wait on the separation, the husband does not provide a living to him, the husband wasted duty as a husband, wife beating, the husband of adultery, impotence, pain parmanen, not able to implement the law of Allah Almighty. The process is starting, sincere intention that after the divorce is still good silaturrahmi both and their families, if the wife nushuz then advise, if it has not changed then separate beds, if not litigious then shot at without a trace properties to educate, if not changed to convey it to the Hakam of the husband and wife, if not get along then convey it to the local religious court to reconcile, then they will process the reconciliation for mediation, if not get along anymore, then wait for the wife of menstruation and then clean the drop tolaq in front of the Religious Court with evidence out certificate of divorce and witnessed two witnesses. Keywords: analysis, the process of divorce, islam Abstrak: Penyebab kebolehan perceraian dari suami adalah ketidakharmonisan dalam rumah tangga, moral dan moral yang krisis, perzinahan, pernikahan tanpa cinta, berlarut-larut perselisihan, parmanen sakit, penjara 5 tahun ke atas, tidak mampu melakukan hubungan suami-istri, tandus istri, tidak mampu menerapkan hukum Allah SWT, istri orang fasik. Talak Khula penyebab lainnya bolehnya suami antar mendapat hukuman penjara selama 5 tahun ke atas, dan istri tidak bisa menunggu pemisahan, suami tidak memberikan nafkah kepadanya, suami terbuang tugas sebagai suami, istri pemukulan, suami dari perzinahan , impotensi, parmanen sakit, tidak mampu melaksanakan hukum Allah SWT. Proses ini dimulai, niat yang tulus bahwa setelah perceraian masih silaturahmi yang baik baik dan keluarga mereka, jika nusyuz istri kemudian menyarankan, jika tidak berubah tempat tidur kemudian terpisah, jika tidak sadar hukum kemudian menembak tanpa jejak sifat mendidik, jika tidak berubah untuk menyampaikan ke Hakam dari suami dan istri, jika tidak bergaul kemudian menyampaikannya ke pengadilan agama setempat untuk mendamaikan, maka mereka akan memproses rekonsiliasi untuk mediasi, jika tidak bergaul lagi, kemudian menunggu istri menstruasi dan kemudian membersihkan talak penurunan di depan Pengadilan Agama dengan bukti keluar surat cerai dan menyaksikan dua saksi.Â Kata Kunci : analisis, proses tolaq, islam